Identification of the GMS friction model based on a robust adaptive observer. (26th February 2009) - Grami, Said; Bigras, Pascal
The identification of the Generalised Maxwell Slip (GMS) friction model is presented in this paper. An approximation is proposed to make the friction model linear over its unknown parameters. A bounded disturbance is used to model the approximation error. A robust observer is then applied to estimate the unknown parameters in spite of the approximation error. The approximated friction model is filtered to render it appropriate for use by the observer. Simulation results are presented to prove the efficiency of the observer in estimating the frictional force even though the model has been approximated.